Sexual and reproductive health in Pakistan: a qualitative exploratory study of gender roles, family planning and adolescent health in Chitral, Gilgit-Baltistan and Sindh - Zulfiqar A Bhutta; Sajid Soofi; Zahid Ali Memon; Tazeen Saeed Ali; Nimira Asif; Farzana Adnan; Maria Farooq; Shahnaz Shahid; Kinza Bhutto; Laraib Lashari; Aamir Sarfaraz; Mir Baz Khan (BMJ Public Health)
Introduction Sexual and reproductive health has been gaining more and more attention due to its all-encompassing definitions and inclusivity of all people, including the marginalised. However, social taboos, lack of political will, broken healthcare system, and sociocultural and economic factors continue to stand as barriers to normalising sexual and reproductive health. This paper explores this topic through focus group discussions and in-depth interviews (IDIs) (exploring both through FGD and direct view from IDIs) in Chitral, Gilgit-Baltistan and Sindh, Pakistan.Methodology This qualitative study was conducted using a descriptive exploratory approach. The target population comprised community members from two districts in Khyber Pakhtunkhwa—Upper and Lower Chitral—as well as two districts in Sindh and six districts in Gilgit-Baltistan. These groups included married adults (aged 18–51), adolescent girls and boys (aged 14–21) and healthcare workforce members. 57 FGDs were conducted with the community and healthcare professionals between October 2020 and December 2020. A purposive sampling technique was used to identify participants, and data analysis was conducted simultaneously with data collection. Consent was obtained from each participant. Qualitative thematic analysis was conducted to identify key themes, through using manual method and NVivo.Results Identified themes include gender inequality, adolescent health, family planning, maternal health and sexual and reproductive health.Discussion Gender inequality in Chitral and Sindh, Pakistan, significantly impacts gaps in the healthcare system, adolescent health, sexual and reproductive health, maternal health, and family planning. The lack of access to healthcare in Chitral and rural Sindh, coupled with gender inequality, significantly impacts family planning. The limited availability of modern contraception and secondary family planning education worsens these difficulties. It will take a broad strategy to address these problems, including initiatives to promote access to family planning services, boost access to education for girls and strengthen the healthcare system in the region.Conclusions There is a need to take a multidimensional approach that promotes women’s empowerment, community involvement and focused investments in healthcare facilities and services to address gender disparity and improve access to healthcare. To accomplish these objectives, it is essential to increase educational accessibility, support gender-sensitive policies and initiatives and invest in the training of the healthcare workforce.